The Harlem Charade - Tarpley, Natasha (New York : Scholastic Press, 2017)
Seventh-graders Jin, Alexandra, and Elvin come from very different backgrounds and circumstances, but they all live in Harlem, and when Elvin's grandfather is attacked they band together to find out who is responsible--and the search leads them to an enigmatic artist whose missing masterpieces are worth a fortune, and into conflict with an ambitious politician who wants to turn Harlem into an historic amusement park.
Keywords: Studio Museum in Harlem -- Juvenile fiction; Studio Museum in Harlem -- Fiction; Political participation. -- Juvenile fiction; African American artists -- Juvenile fiction; Community development -- Juvenile fiction -- New York (State); Political participation. -- Fiction; African American artists -- Fiction; Community life -- Fiction; Mystery and detective stories; Harlem (New York, N.Y.) -- Juvenile fiction; New York, N.Y. -- Juvenile fiction; Harlem (New York, N.Y.) -- Fiction; New York (N.Y.) -- Fiction